Computational modelling of nanofluid flow over a curved stretching sheet using Koo–Kleinstreuer and Li (KKL) correlation and modified Fourier heat flux model. (April 2021) - Punith Gowda, R.J.; Al-Mubaddel, Fahad S.; Naveen Kumar, R.; Prasannakumara, B.C.; Issakhov, Alibek; Rahimi-Gorji, Mohammad; Al-Turki, Yusuf A.
Highlights: Flow and heat transfer characteristics of nanoliquid by using Koo–Kleinstreuer and Li (KKL) correlation is studied. Modified Fourier heat flux law is utilised to model the temperature equation. Viscous dissipation, activation energy and chemical reaction effects are used to study heat and mass transfer characteristics. Accurate numerical solutions are obtained using Runge-Kutta-Fehlberg fourth fifth order along with shooting technique. Abstract: The objective of the current paper is to study the two-dimensional, incompressible nanofluid flow over a curved stretching sheet coiled in a circle. Further, the impact of dispersion of nanoparticle CuO in base liquid water on the performance of flow, thermal conductivity and mass transfer using KKL model in the presence of Cattaneo-Christov heat flux and activation energy is deliberated. A curvilinear coordinate system is used to develop the mathematical model describing the flow phenomena in the form of partial differential equations. Further, by means of apt similarity transformations the governing boundary value problems are reduced to ordinary differential equations. Mathematical computations are simplified using Runge-Kutta-Fehlberg-45(RKF-45) process by adopting shooting method. Graphical illustrations of velocity, temperature, concentration gradients for various pertinent parameters are presented. The result reveals that, the heightening of porosity parameter heightens the thermal gradient but converse trend is depicted in velocity gradient. The enhancing values of Schmidt number and chemical reaction rate parameter declines concentration gradient whereas converse trend is depicted for upsurge in activation energy parameter.